The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1103/physrevd.98.095021
|View full text |Cite
|
Sign up to set email alerts
|

New phenomenological and theoretical perspective on anomalous ZZ and Zγ processes

Abstract: Neutral diboson processes are precise probes of the Standard Model (SM) of particle physics, which entails high sensitivity to new physics effects. We identify in terms of dimension-8 effective operators the leading departures from the SM that survive in neutral diboson processes at high energy and that interfere with the unsuppressed SM helicity contributions. We describe symmetries and selection rules that single out those operators, both for weakly and strongly coupled physics beyond the SM. Finally, we sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 46 publications
0
69
0
Order By: Relevance
“…Such relations, often denoted as sum rules, can be classified in terms of the energy expansion of the amplitudes analogous to the EFT operator expansion. In previous works, the main focus has been at the level of dimension-8 operators for which the sum rules can be interpreted as positivity bounds on certain operator coefficients (or combinations of them) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This remarkable finding suggests that the possible parameter space in an EFT is already constrained by the fundamental properties of quantum field theory, i.e.…”
Section: Jhep03(2021)149mentioning
confidence: 99%
See 2 more Smart Citations
“…Such relations, often denoted as sum rules, can be classified in terms of the energy expansion of the amplitudes analogous to the EFT operator expansion. In previous works, the main focus has been at the level of dimension-8 operators for which the sum rules can be interpreted as positivity bounds on certain operator coefficients (or combinations of them) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This remarkable finding suggests that the possible parameter space in an EFT is already constrained by the fundamental properties of quantum field theory, i.e.…”
Section: Jhep03(2021)149mentioning
confidence: 99%
“…can be imposed by requiring the isospins of f to satisfy either 12) which are exactly the same conditions in ref. [59] for protecting the SM Zff coupling.…”
Section: Jhep03(2021)149mentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that only a finite number of helicity amplitudes get corrections up to the given EFT order, see for instance refs. [45,46]. The coefficients of these basis functions, the so called angular moments [47][48][49][50], and their energy dependance, thus, contain the full differential information available in a process.…”
Section: Jhep09(2020)170mentioning
confidence: 99%
“…It has been shown that, at the LHC, several simple two-body production channels can be exploited to obtain precision measurements [1][2][3][4][5][6][7][8]. Among them, diboson production processes, featuring EW gauge bosons or the Higgs boson, play a privileged role since they can be used to indirectly test the high-energy Higgs dynamics [5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%